MENINGKATKAN EFEKTIVITAS PEMBELAJARAN MELALUI APLIKASI GAME EDUKASI BERBASIS ANDROID - Nur Ayu Annisa; Isti Rusdiyani; Lukman Nulhakim (Akademika, 2022)
Interesting learning media innovations have an impact on the quality of the process and learning outcomes .Optimization effort smartphone students in learning activities namely by integrating interactive multimedia into Smartphone based android Development of the 4-D model which has four main stages, namely; define, design, develop, and disseminate. The purpose of the study was to determine the effectiveness of using Android-based educational game learning media on learning outcomes..This type of screening research is development research or Research and Development (R&D) with developed media is learning media in the form game education based android . The object of this development research is students in SMAN 1 Cigemblong to be exact class XI. Quantitative data analysis to test the effectiveness of learning media products using Tests N - Gain Score. Based on learning media development products game education based android that the average value results pre-test and post-test it's 0.73. Based on the reference value if the value of g>0.7 then falls into the "high" category, thus based on these results the use of the product that has been developed affects the effectiveness of learning.